Species delimitation of the praying mantis Hierodula patellifera (Audinet-Serville) based on morphological and molecular characters (Mantodea: Mantidae) - Shim, Jaeil; Park, Haechul; Kim, Seonghyun; Ju, Ho-Jong; Song, Jeong-Hun (Zootaxa, 2021)
An integrative taxonomic analysis of Hierodula patellifera (Audinet-Serville) is presented based on morphological and molecular characters (COI, 28S rDNA). During repeated trips to the Korean peninsula, we collected unusual specimens from Wanju-gun. They were similar to H. patellifera, but can be distinguished by a larger body size, the number and shape of spines on foreleg, and the shape of male genitalia. To examine the phenotypes and delimit H. patellifera from fourteen sampled populations, we used forecoxal spines and male genitalia as key morphological characters, as well as molecular data including gene tree monophyly and genetic divergence data. The molecular analyses (p-distance, neighbor-joining, and parsimony analyses) did not separate the specimens as two distinct species. The diagnostic characters of H. patellifera are illustrated with habitus images.